2021
DOI: 10.1152/jn.00629.2020
|View full text |Cite
|
Sign up to set email alerts
|

The role of eye movements, attention, and hand movements on age-related differences in pegboard tests

Abstract: Well-documented manual dexterity impairments in older adults may critically depend on the processing of visual information. The purpose of this study was to determine age-related changes in eye and hand movements during commonly used pegboard tests and the association with manual dexterity impairments in older adults. The relationship between attentional deficits and manual dexterity was also assessed. Eye movements and hand kinematics of 20 young (20-38 years) and 20 older (65-85 years) adults were recorded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass (Soyuer et al, 2023), reduced coordination or neuromuscular impairments (Carson, 2018; Clark, 2019), as well as changes in sensory, visual, and attention capabilities (Heintz Walters et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass (Soyuer et al, 2023), reduced coordination or neuromuscular impairments (Carson, 2018; Clark, 2019), as well as changes in sensory, visual, and attention capabilities (Heintz Walters et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass ( Soyuer et al, 2023 ), reduced coordination or neuromuscular impairments ( Carson, 2018 ; Clark, 2019 ), as well as changes in sensory, visual, and attention capabilities ( Heintz Walters et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progressive effects of these correlated changes can also interact and compound, leading to more complex design challenges. For example, a recent eye‐tracking study of older adults observed Age‐associated changes in eye movement correlated with reduced manual dexterity [HWHO*21]. These observations complicate some traditional interaction paradigms, such as pinch‐to‐zoom: the people for whom zooming would serve as an adaptive strategy may have difficulty performing the physical gesture required to access it.…”
Section: Adjacent Areas Of Studymentioning
confidence: 99%